Longitudinal changes in body composition and waist circumference by self-reported levels of physical activity in leisure among adolescents: the Tromsø Study, Fit Futures - Aars, Nils Abel; Jacobsen, Bjarne Koster; Morseth, Bente; Emaus, Nina; Grimsgaard, Sameline (BMC Sports Science, Medicine and Rehabilitation, 2019)
Background - It is not clear how physical activity affects body composition in adolescents. Physical activity levels are often reduced during this period, and the relative proportion of body fat mass and lean mass undergo natural changes in growing adolescents. We aimed to examine whether self-reported physical activity in leisure time at baseline or change in activity during follow-up affect changes in four measures of body composition; body mass index (kg/m 2 ), waist circumference, fat mass index (fat mass in kg/m 2 ) and lean mass index (lean mass in kg/m 2 ). Methods - We used data from the Tromsø Study Fit Futures, which invited all first year students in upper secondary high school in two municipalities in northern Norway in 2010–2011. They were reexamined in 2012–2013. Longitudinal data was available for 292 boys and 354 girls. We used multiple linear regression analyses to assess whether self-reported level of physical activity in leisure time at baseline predicted changes in body composition, and analysis of covariance to assess the effects of change in level of activity during follow-up on change in body composition. All analyses were performed sex-specific, and a p -value of < 0.05 was considered statistically significant. Results - There were no associations between self-reported leisure time physical activity in the first year of upper secondary high school and changes in any of the considered measure of body composition after 2 years of follow up, with the exception of waist circumference in boys ( p = 0.05). In boys, change in fat mass index differed significantly between groups of activity change ( p < 0.01), with boys adopting activity or remaining physically active having less increase in fat mass index than the consistently inactive. In girls, change in lean mass index differed significantly between groups of activity change ( p = 0.04), with girls adopting physical activity having the highest increase. Conclusions - Self-reported leisure time physical activity does not predict changes ...